Serum Protein Total Determination After Hypoxic Swimming Exercises in Trained and Untrained Swimmers Using The Nanophotometric Method - Siska Alicia Farma; Syahrastani Syahrastani (Bioscience, 2021)
Anaerobic physical exercise aims to increase the explosive power, which is the ability of a person's muscles to do work with maximum strength in the fastest possible time. Sprint swimming exercises are often called hypoxic swimming exercises. Protein biomolecules have a major function in building muscle mass, maintaining body defences and increasing sports performance. Physical exercise occurs in a variety of systemic and cellular responses involving metabolic, immunological and hormonal changes. It is necessary to know how the total protein profile in serum after physical exercise in this case was limited to a single hypoxic swimming exercise. This was experimental research with post-test only control group design. There were three training groups, namely (5) control, (5) trained, and (5) untrained based on inclusion and exclusion criteria with the purposive sampling method. Single hypoxic swimming exercise (sprint) did along 200 m. The swimming training pattern was per 50 m without resting with two types of styles swim, freestyle and breaststroke. Measurement of total protein levels was carried out using a nanophotometer where the volume of serum used was very small. The results showed that the total protein content between the control group and the treatment group was significantly different (ANOVA, p <0.05). Between the trained and untrained groups, a decrease in total protein levels was seen in the trained group. This is probably due to the function of these proteins. It can be concluded that protein is more widely used by the body as a building element in the body, especially muscle mass. Cellular adaptive response is better when the body is in a trained condition.